Exploring plant growth promoting traits and biocontrol potential of new isolated Bacillus subtilis BS-2301 strain in suppressing Sclerotinia sclerotiorum through various mechanisms - Ayaz, Muhammad; Ali, Qurban; Zhao, Wei; Chi, Yuan-Kai; Ali, Farman; Rashid, Khan Abdur; Cao, Shun; He, Yan-qiu; Bukero, Abdul Aziz; Huang, Wen-Kun; Qi, Ren-De (Frontiers in Plant Science, 2024)
Sclerotinia sclerotiorum (Lib.) de Bary is the causative agent of stem white mold disease which severely reduces major crop productivity including soybean and rapeseed worldwide. The current study aimed to explore plant growth-promoting traits and biocontrol of new isolated Bacillus subtilis BS-2301 to suppress S. sclerotiorum through various mechanisms. The results indicated that the BS-2301 exhibited strong biocontrol potential against S. sclerotiorum up to 74% both in dual culture and partition plate experiments. The BS-2301 and its crude extract significantly suppressed S. sclerotiorum growth involving excessive reactive oxygen species (ROS) production in mycelia for rapid death. Furthermore, the treated hyphae produced low oxalic acid (OA), a crucial pathogenicity factor of S. sclerotiorum. The SEM and TEM microscopy of S. sclerotiorum showed severe damage in terms of cell wall, cell membrane breakage, cytoplasm displacement, and organelles disintegration compared to control. The pathogenicity of S. sclerotiorum exposed to BS-2301 had less disease progression potential on soybean leaves in the detached leaf assay experiment. Remarkably, the strain also demonstrated broad-range antagonistic activity with 70%, and 68% inhibition rates against Phytophthora sojae and Fusarium oxysporum, respectively. Furthermore, the strain exhibits multiple plant growth-promoting and disease-prevention traits, including the production of indole-3-acetic acid (IAA), siderophores, amylases, cellulases and proteases as well as harboring calcium phosphate decomposition activity. In comparison to the control, the BS-2301 also showed great potential for enhancing soybean seedlings growth for different parameters, including shoot length 31.23 %, root length 29.87 %, total fresh weight 33.45 %, and total dry weight 27.56 %. The antioxidant enzymes like CAT, POD, SOD and APX under BS-2301 treatment were up-regulated in S. sclerotiorum infected plants along with the positive regulation of defense-related genes (PR1-2, PR10, PAL1, AOS, CHS, and PDF1.2). These findings demonstrate that the BS-2301 strain possesses a notable broadspectrum biocontrol potential against different phytopathogens and provides new insight in suppressing S. sclerotiorum through various mechanisms. Therefore, BS-2301 will be helpful in the development of biofertilizers for sustainable agricultural practices.